Implementasi Monitoring dan Evaluasi Pelaksanaan Supervisi Pembelajaran di Madrasah - A Faizul Mubarak (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
This article discusses the implementation of monitoring and evaluation of the implementation of learning supervision in Madrasahs. The findings of this article are that the academic professional supervision of school supervisors is the authority of madrasa supervisors as a supervisory activity for teachers in an effort to improve and improve the quality of teaching, should be directed at improving the behavior of professional performance of teachers to serve students, create cooperative learning strategies and develop learning quality.